Analisis Variabel Fundamental yang Berpengaruh terhadap Price Earning Ratio (PER) sebagai Dasar Penilaian Saham pada Perusahaan Automotive and Allied yang Terdaftar di Bursa Efek Indonesia - Rahma, Erlin Yulia; Djazuli, Atim; Djumahir (Universitas Brawijaya, Indonesia, 2014)
The goal of this research is to analyze the fundamental variables in which influinfluence price earning ratio of automotive and allied companies which are listed in Indonesia Stock Exchange. These variables are return on equity, debt equity ratio, earning per share, dividend payout ratio, price to book value and earning growth. The data collection is using sampling technique, there is saturated sampling or sample census. The result shows that there are six companies along 2007 to 2011. The analysis technique uses multiple linear regression in order to check the influence of independent variable on dependent variable. The result shows that the variable of return on equity is giving negative sign significant to the price earning ratio. Next, price to book value variable influences positively and signifisignificant to the price earning ratio. Coefficient determinant which is achieved is 0,536, which means that the prediction power of regression model is 53,6%.